Temperature and Lighting Control of Deep Water Culture Hydroponic System in Automatic Miniroom Space - Kurniawan Dwi Yulianto; Riky Dwi Puriyanto (Buletin Ilmiah Sarjana Teknik Elektro, 2023)
This research will develop a temperature control system and lighting using LEDs on automatic indoor hydroponic plants. The process of monitoring air temperature, light intensity and time in real time in a miniroom using a DHT-11 sensor, BH-1750 sensor, RTC, and Arduino Uno for data processing. The results of this study indicate that the prototype made can work well. The DHT-11, BH-1750 and RTC sensors used in this study can work optimally. Temperature measurement using the DHT-11 Sensor has an Error value of 1.44% and Light Intensity Measurement using the BH-1750 Sensor has an Error value of 2.48% so that it can be used and applied to the system. This research works as expected where the system created can control the indoor temperature and lighting duration in the indoor hydroponic system.